PRINCIPLES OF RESPONSIBILITY OF BUSINESSES FOR THE ADDITION OF EXONERATION CLAUSULES IN ELECTRONIC TRANSACTIONS THROUGH INTERNET WEBSITES REVIEWED FROM THE LEGAL PERSPECTIVE OF CONSUMER PROTECTION - Bisma (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
In this study the focus on exoneration clauses in online / online site electronic transactions can place an unbalanced position between businesses and consumers. Business actors freely include exoneration clauses in online / online sites for the purpose of legal protection for the business actors themselves. Thus, this dissertation research is research on